2014
DOI: 10.1517/14728222.2014.983078
|View full text |Cite
|
Sign up to set email alerts
|

Circulating semaphorin-4D and plexin-B1 levels in postmenopausal women with low bone mass: the 3-month effect of zoledronic acid, denosumab or teriparatide treatment

Abstract: Sema4D levels are independently associated with previous bisphosphonate treatment, intact parathyroid hormone and 25(OH)D levels. Denosumab and teriparatide seem to exert an opposite effect on circulating sema4D levels. Further studies are needed to evaluate whether sema4D mediates the coupling effect that occurs following both antiresorptive and osteoanabolic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…It was also reported that another bone resorption inhibitor, denosumab, increased sclerostin levels at 6 months and maintained the levels thereafter [ 10 ]. On the other hand, no significant increase in PTH was observed after 3 months of treatment with denosumab [ 24 ], suggesting that the relationship between changes in levels of PTH and levels of sclerostin may differ depending on the type of bone resorption inhibitor used for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that another bone resorption inhibitor, denosumab, increased sclerostin levels at 6 months and maintained the levels thereafter [ 10 ]. On the other hand, no significant increase in PTH was observed after 3 months of treatment with denosumab [ 24 ], suggesting that the relationship between changes in levels of PTH and levels of sclerostin may differ depending on the type of bone resorption inhibitor used for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Different effects of bone-targeted therapies on Sema4D have already described in postmenopausal women suffering from low bone mass. Circulating levels of Sema4D were increased by denosumab, but decreased following treatment with teriparatide [26]. Sema4D is produced by osteoclasts and suppresses IGF-1 signaling in osteoblasts, thereby inhibiting bone formation [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Plexin-B1, the secreted ectodomain may be the result of alternative splicing or of proteolytic cleavage of the full-length protein from the cell membrane (Tamagnone et al, 1999;Artigiani et al, 2003;Ito et al, 2014). Recently, increased levels of a soluble, circulating Plexin-B1 portion were found in postmenopausal women with low bone mass (Anastasilakis et al, 2015); a secreted extracellular part of Plexin-B1 was also detected in proteomics studies (Farrah et al, 2011). Moreover, we detected soluble forms of Plexin-B1 of ∼70 kD in size released from lymphatic endothelial cells (HMV ECs).…”
Section: Discussionmentioning
confidence: 99%